Há variação na distribuição e abundância das espécies de camarões-rosa, Farfantepenaeus spp. (Dendrobranchiata: Penaeidae) no litoral norte do estado de São Paulo? - Said, João Guilherme Iken [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Este estudo analisou a variação espacial e temporal na abundância e distribuição das espécies congêneres Farfantepenaeus paulensis e F. brasiliensis na região externa da Baía de Ubatuba, litoral norte do estado de São Paulo, e avaliou a influência de fatores ambientais sobre suas populações. As coletas foram realizadas mensalmente ao longo de 2000, em cinco pontos de diferentes profundidades (20 à 40 m), onde também foram mensurados valores de temperatura, salinidade, teor de matéria orgânica e granulometria do sedimento. Foram capturados 481 indivíduos, sendo 401 de F. brasiliensis e 80 de F. paulensis. As fêmeas exibiram comprimento de carapaça significativamente maior que os machos, condição relacionada a uma estratégia reprodutiva que pode conferir uma maior fecundidade. A razão sexual foi enviesada a favor dos machos em F. brasiliensis, especialmente no outono e em maiores profundidades, e próxima do equilíbrio em F. paulensis. As análises estatísticas indicaram que F. brasiliensis foi significativamente mais abundante, com pico em 35 m e sedimentos de areia fina, enquanto F. paulensis predominou em 25 m. Ambas apresentaram maior abundância no outono, sob temperaturas médias de 20 °C e salinidades próximas de 35psu. As diferenças de tamanho, abundância e distribuição sugerem partição de habitat mediada por tolerância fisiológica e competição interespecífica. Os resultados encontrados podem ampliar o conhecimento sobre a ecologia das espécies e subsidiar ações de manejo e revisão dos períodos de defeso da pesca do camarão-rosa no litoral paulista.

This study analyzed the spatial and temporal variation in the abundance and distribution of the congeneric species Farfantepenaeus paulensis and F. brasiliensis in the outer region of Ubatuba Bay, on the northern coast of the state of São Paulo, and evaluated the influence of environmental factors on their populations. Samples were collected monthly throughout 2000 at five points at different depths (20 to 40 m), where temperature, salinity, organic matter content, and sediment grain size were also measured. Samples were collected monthly throughout 2000 at five points at different depths (20 to 40 m), where temperature, salinity, organic matter content, and sediment grain size were also measured. A total of 481 individuals were captured, 401 of which were F. brasiliensis and 80 were F. paulensis. The females exhibited significantly greater carapace length than the males, a condition related to a reproductive strategy that may confer greater fecundity. The sex ratio was skewed in favor of males in F. brasiliensis, especially in the fall and at greater depths, and close to equilibrium in F. paulensis. Statistical analyses indicated that F. brasiliensis was significantly more abundant, peaking at 35 m and fine sand sediments, while F. paulensis predominated at 25 m. Both species were more abundant in autumn, under average temperatures of 20 °C and salinities close to 35 psu. The differences in size, abundance, and distribution suggest habitat partitioning mediated by physiological tolerance and interspecific competition. The results found may expand knowledge about the ecology of the species and support management actions and revision of the closed seasons for pink shrimp fishing on the coast of São Paulo.
Is there variation in the distribution and abundance of pink shrimp species, Farfantepenaeus spp. (Dendrobranchiata: Penaeidae), along the northern coast of the state of São Paulo?
Keywords: Baía de Ubatuba; Congênere; Fatores abióticos; Partição de habitat; Pesca